Renal Cell Carcinoma With Leiomyomatous Stroma: A Group of Tumors With Indistinguishable Histopathologic Features, But 2 Distinct Genetic Profiles: Next-Generation Sequencing Analysis of 6 Cases Negative for Aberrations Related to the VHL gene - Petersson, Fredrik; Martinek, Petr; Vanecek, Tomas; Pivovarcikova, Kristyna; Peckova, Kvetoslava; Ondic, Ondrej; Perez-Montiel, Delia; Skenderi, Faruk; Ulamec, Monika; Nenutil, Rudolf; Hora, Milan; Svoboda, Tomas; et al. (Applied immunohistochemistry & molecular morphology, 2018)
We have studied a cohort of renal cell carcinomas (RCCs) with smooth-muscle stroma (N=6), which lacked any of following genetic aberrations: mutations in the VHL-gene-coding sequence, loss of heterozygosity of chromosome 3p, or hypermethylation of VHL. Using targeted next-generation sequencing, no intronic VHL mutations or mutations in selected genes involved in angiogenesis and genes frequently mutated in clear cell RCC were identified. Tumors were also tested for the presence of hotspot mutations in the TCEB1 gene with negative results in all cases. We conclude that there exists a group of RCCs with abundant leiomyomatous stroma, where the epithelial component is indistinguishable from conventional clear cell RCC and distinct from clear cell (tubulo-) papillary RCC and that these tumors lack aberrations related to the function of the VHL gene, mutations in genes involved in angiogenesis, and hotspot mutations in the TCEB1 gene.
Keywords: vysoce účinné nukleotidové sekvenování; Male; lidé středního věku; nádorový supresorový protein VHL; Carcinoma, Renal Cell; Mutation; Von Hippel-Lindau Tumor Suppressor Protein; Humans; Middle Aged; karcinom z renálních buněk; senioři; mužské pohlaví; Female; Aged; Leiomyosarcoma; ženské pohlaví; genetické testování; leiomyosarkom; mutace; lidé; High-Throughput Nucleotide Sequencing; Genetic Testing